Pengaruh sistem zero waste werhadap pola konsumsi sampah di Pondok Pesantren Al-Anwar 3 Sarang - Faz, Najma Tsuroyya (Maliki Interdisciplinary Journal, 2024)
The waste produced by Islamic boarding schools is more than the waste produced by households. Al-Anwar 3 Islamic Boarding School in Sarang sub-district, Rembang is one of the Islamic boarding schools that implements a zero waste system as part of its daily activities. The researcher conducted this analysis aims to analyze the effect of the zero waste system on waste consumption patterns and environmental awareness of students at the Al-Anwar 3 Islamic Boarding School. This research uses a qualitative approach to gain an in-depth understanding. The results of this study indicate that the implementation of a zero waste system in the boarding school such as sorting waste and classifying waste, cultivating lava maggot, using meal boxes and tumblers, and finally waste will be managed independently by the Al Anwar 3 Waste Management Center. The challenge faced in implementing a zero waste system in the boarding school is the self-awareness of the students.